2009
DOI: 10.1089/ees.2008.0408
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Chemical Dispersant Efficacy in an Experimental Wave Tank: 2—Significant Factors Determining In Situ Oil Droplet Size Distribution

Abstract: Chemical dispersion is one of the most cost-effective options to remediate oil spill at open sea. Identifying significant factors that determine in situ droplet size distributions facilitates mechanistic understanding of dispersant effectiveness. In this work, in situ dispersed oil droplet size distributions were characterized during testing of chemical dispersant effectiveness of two dispersants (Corexit 9500 and SPC 1000) on two oils [Medium South American (MESA) and Alaska North Slope (ANS)] under three wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 25 publications
5
30
1
Order By: Relevance
“…Indeed, surfactants increase solubilization of hydrocarbons by forming micelles which will limit the adhesion of oil compounds and stabilize oil droplets. On the contrary, droplets of oil in the MD condition could form more aggregates because of their strong hydrophobic properties and their greater size compared to the CD condition (Li et al, 2009). The results obtained on the size of oil droplets in this study tend to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, surfactants increase solubilization of hydrocarbons by forming micelles which will limit the adhesion of oil compounds and stabilize oil droplets. On the contrary, droplets of oil in the MD condition could form more aggregates because of their strong hydrophobic properties and their greater size compared to the CD condition (Li et al, 2009). The results obtained on the size of oil droplets in this study tend to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 62%
“…1). Additional details on the wave tank can be found in Li et al (2009aLi et al ( , 2009bLi et al ( , 2009c and King et al (2013King et al ( , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Various oil spill countermeasures were considered and applied to CLB, which are as follows: no treatment, usage of dispersant (Corexit 9500), usage of the mineral fines (MF, Kaolinite clay), and a combination of dispersant + MF. The selected oil spill countermeasures have been successfully used in the past to disperse conventional crude oils in the water column to generate droplet sizes less than 70 lm (Li et al, , 2009a(Li et al, , 2009b(Li et al, , 2009c(Li et al, , 2010. The results sought in this work will improve our knowledge on the fate and transport of diluted bitumen products spilled at sea and how their fate is influenced by oil spill countermeasures.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Very few studies have shown a comprehensive physical characterization of the particulate oil in the test media and the methods used for this purpose often lack of standardization (microscopy) , do not have enough selectivity towards oil droplets (Coulter Counter particle analyzer) (Hansen et al, 2009;Nordtug et al, 2011a), are limited by the technology used (Laser In-Situ Scattering and Transmissometry, LISST) (Conmy et al, 2014;Li et al, 2011;Li et al, 2009;Trudel et al, 2010) or conducted after the fact by complex solubility calculations once the full chemical characterization is completed (Redman et al, 2012a). All these limitations prevent timely feedback on the evolution of the mixtures before, during and after the test which could be used to manage the longer periods of time required for chronic toxicity testing (> 7 days).…”
Section: Characterization Of Oil Water Mixturesmentioning
confidence: 99%